Dynamics of ligand and nanobody binding at CXCR4/EGFR complexes - Comez, Dehan (2025)
Understanding the cell signalling of cancer has the potential to impact the development of anti-cancer therapeutics. The dimerisation of cell membrane receptors is one of the key modulators of cancer cell signalling. G-protein coupled receptors (GPCRs) and receptor tyrosine kinases (RTKs) are two prominent receptor families regulating various cellular processes in normal physiology and cancer progression. The abnormalities in membrane receptors, such as mutations, overexpression or enhanced receptor-receptor interaction are relevant for many cancer types. CXCR4 is significantly upregulated in numerous cancers, which correlates to cancer progression. Epidermal growth factor receptor (EGFR) is one of the major growth hormone receptors critical to various cancers, promoting cancer progression, proliferation, survival, and metastasis. This thesis aimed to elucidate the dynamics of CXCR4 and EGFR complexes. NanoLuciferase Bioluminescence Resonance Energy Transfer (NanoBRET) was used to quantify interacting characteristics of CXCR4/EGFR dimerisation with NanoLuciferase and fluorophore tags on receptors. Proximity Ligation Assay (PLA) was also used to detect endogenously expressed CXCR4/EGFR dimers on HeLa cells with receptor specific nanobodies conjugated to oligonucleotides. We have shown that, in the presence of the NLuc substrate furimazine, energy transfer occurs from NLuc-tagged donor (NLuc_EGFR or NLuc_CXCR4) to the closely located acceptor fluorophore- tagged receptor (SNAP_CXCR4 or HaloEGFR). Similar results were observed for oligonucleotide conjugated nanobody-based proximity ligation assay (PLA) with endogenously expressed or CRISPR-edited CXCR4/EGFR. Additionally, the dynamics of various receptor selective agonists/antagonists (CXCL12, EGF, TGF-α, AMD3100, IT1t, Erlotinib, etc.) and nanobodies (VUN400, Q44, etc.) binding at CXCR4/EGFR complex, demonstrated monomerising or dimerising effects. These data revealed that there is close proximity (<10nm) between EGFR and CXCR4 on the cellular membrane, and this proximity can be impacted by several EGFR/CXCR4 receptor ligands and nanobodies. These data improve our understanding of CXCR4/EGFR complex and its potential therapeutic utilization especially for cancer biology.